Similarity evaluation in XML schema and XLink - Mota, Marta; Silva, Paulo Caetano da; Viana, Sidney (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
XML SCHEMA is a standard defined by W3C widely used in the specification of XML elements. Another standard by W3C is XML Linking Language (XLink), a language that specifies how elements should be declared in XML documents in order to define links between two or more resources. XLink and XML Schema are emerging Internet standards applied in varying contexts such as XBRL Language. Similarity evaluation is an important process in data management and serves as support for one of its core activity: duplicate detection. Thus, the classification of XML elements according to the similarity between them is becoming increasingly useful in the area of XML data management. This paper presents a process for similarity evaluation between XML elements defined with the use of XML Schema and XLink and an experiment. The experiment applies the proposed process to the context of the XBRL concepts, an example of XML elements created with extensive use of XML Schema and XLink.